ANALYSIS OF VAK STUDENT LEARNING STYLE PGSD UKI TORAJA - Mersilina Luther Patintingan; Reni Lolotandung (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2021)
One of the factors that affect a person's learning outcomes is their learning style(Aryo Andri Nugroho, Ida Dwijayanti 2017). The division of student classes, taking into account each individual's learning styles; will greatly aid instructors in preparing teaching methods and materials that are appropriate for the students' learning styles. The VAK (Visual, Auditory and Kinesthetic) learning style was developed by Rita Dunn and Kennenth Dunn(Lehmann dan Ifenthaler 2012). Children with visual learning styles typically learn through external visual relationships, children with auditory learning styles learn more easily through listening, and children with kinesthetic learning styles learn through physical movements to input information into their brain(Sari n.d.).The aim of this study is to describe the results of the VAK analysis of the learning style (visual, auditory and kinesthetic) of students in the UKI Toraja PGSD study program in order to address issues related to the National Research Master Plan (RIRN) on Social Humanities, Cultural Arts, and education bureau can solve. Domestic studies on educational and learning technology. This research will be carried out in 3 (three) stages. The first phase was to observe the VAK (Visual, Auditory and Kinesthetic) learning style of the UKI Toraja PGSD study program students. In the second phase, data was collected and direct interviews were conducted with relevant sources on the VAK (Visual, Auditory and Kinesthetic) learning style of students in the UKI Toraja PGSD study program. The third phase is to manage and analyze the results of face-to- face interviews and to publish the results of research on the VAK learning styles (visual, auditory and kinesthetic) of students in the UKI Toraja PGSD study program. The results of the analysis of the VAK learning style of students in the UKI Toraja PGSD study program for the 2019/2020 academic year. This research is a descriptive study with a qualitative approach. The subjects of this study were all students in the 2018/2019 primary school teacher-training course. The instrument used in this study was a questionnaire, the content of which was adapted from 18 elements from the versions of Rita and Kenneth Dunn. These are then grouped into 6 subsections of learning styles that are common to students, namely: Visual, Auditory, and Kinesthetic. The data analysis used in this study is a descriptive analysis using statistical methods. Based on the results of the analysis of the study style questionnaire of 2018 UKI Toraja PGSD students, of which the respondents were 282 students, the auditory was 34.2%, the visual 44.7% and the kinesthetic 21.1%. From the above data, it can be concluded that the class of PGSD students in 2018 has a predominantly visual learning style.